A life course approach to chronic disease epidemiology - Kuh, Diana; Ben-Shlomo, Yoav. (Oxford : Oxford University Press, 2004)
'A Life Course Approach to Chronic Disease Epidemiology' provides a detailed and up-to-date review of research findings which suggest that many of the chronic diseases prevalent in adult life have their origins in early life.
Previous ed.: 1997.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chronic diseases -- Etiology; Chronic diseases -- Epidemiology; Health expectancy